2020
DOI: 10.1088/1361-6528/ab98bb
|View full text |Cite
|
Sign up to set email alerts
|

Development of high-performance sensor based on NiO/SnO2 heterostructures to study sensing properties towards various reducing gases

Abstract: In this work, we report the spontaneous formation of NiO nanoparticles-decorated onto smooth SnO2 nanofibers, which is an inexpensive and scalable method for yielding a high composite surface area via a simple two-step synthesis process based on electrospinning and the hydrothermal method. A Nickel Oxide proton-conducting electrolyte is deposited homogeneously over a large surface area in a transparent solution, mixed and decorated onto Tin dioxide nanofibers, as evidenced by cross sectional imaging of the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…The SnO 2 −NiO nanopattern sensor shows a faster response time due to the catalytic effect of NiO enabling a lower activation energy for dissociation of analytes and O 2 . 29,30 To check the detection selectivity, we tested cross-sensitivity of the sensors to a total of 11 different gases compared to H 2 S (Figure 5c). We selected VOCs (toluene, hexane, propanal, acetone, ethanol), reducing gases (NO, NH 3 , H 2 ), and oxidizing gases (SO 2 , CO 2 , NO 2 ) as reference gases for two reasons: First, VOCs are easily found in exhaled breath of human to detect halitosis, and second, reducing and oxidizing gases are easily found in industrial monitoring.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SnO 2 −NiO nanopattern sensor shows a faster response time due to the catalytic effect of NiO enabling a lower activation energy for dissociation of analytes and O 2 . 29,30 To check the detection selectivity, we tested cross-sensitivity of the sensors to a total of 11 different gases compared to H 2 S (Figure 5c). We selected VOCs (toluene, hexane, propanal, acetone, ethanol), reducing gases (NO, NH 3 , H 2 ), and oxidizing gases (SO 2 , CO 2 , NO 2 ) as reference gases for two reasons: First, VOCs are easily found in exhaled breath of human to detect halitosis, and second, reducing and oxidizing gases are easily found in industrial monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…Real-time sensor data for various H 2 S concentration and response/recovery time are shown in Figures S6 and S7, respectively (performance of SnO 2 –Au is shown in Figure S8). The SnO 2 –NiO nanopattern sensor shows a faster response time due to the catalytic effect of NiO enabling a lower activation energy for dissociation of analytes and O 2 . , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and/or p-type (CuO, NiO, Co 3 O 4 etc.) metal oxides that show different sensing properties depending on the way they are formed. Various studies revealed that the existence of such heterojunctions facilitates gas sensing phenomenon by electron/hole movement through the interface modulated potential barrier. When two different metal oxides are in physical contact, the Fermi level of the hybrid material must align.…”
Section: Oxide Heterostructure For Gas Sensingmentioning
confidence: 99%
“…In recent years, NiO has been reported to recombine with n-type semiconductors such as ZnO [63,[100][101][102][103][104][105][106][107][108][109][110], SnO 2 [67,[111][112][113][114][115][116][117][118], WO 3 [119][120][121], Fe 2 O 3 [122][123][124], and In 2 O 3 [125,126].…”
Section: Metal Oxidesmentioning
confidence: 99%